The Occurrence Of Geomagnetic Storm In Solar Cycles 23 And 24 And Their Correlation With Cycle Peaks - Juangsih, Mira; Nuraeni, Fitri; Ratnasari, Elvina; Hakim, Lukmanul (Indonesian Journal of Aerospace, 2024)
The 23rd solar cycle occurred from 1996 to 2008, while the 24th solar cycle occurred from 2009 to 2020. Throughout the cycles there were various solar activities that caused geomagnetic storm such as high speed stream (HSS), co-rotating interaction region (CIR), and coronal mass ejection (CME). By using Disturbance storm time (Dst) index, we identified 243 storms during cycle 23 and 149 storms during cycle 24. The distribution of geomagnetic storms corresponds to the distribution of the solar cycle based on sunspot numbers. The cycle 23 exhibited higher activity with 84 strong to extreme storms compare to cycle 24 which had 22 strong to very strong storms. In both cycles, 65% moderate geomagnetic storms were caused by the high speed stream, whereas 85% of strong geomagnetic storms were caused by CMEs. In this study, both cycles exhibit distinct characteristic in producing geomagnetic storms. The low or high maximum phase of a cycle is not associated with the frequency occurrence of strong to extreme geomagnetic storms; both cycles show comparable results in this regard. However a longer declining phase of solar cycle has more impact on production of more moderate storms